2012
DOI: 10.1159/000342710
|View full text |Cite
|
Sign up to set email alerts
|

What Attitudes and Needs Do Citizens in Europe Have in Relation to Complementary and Alternative Medicine?

Abstract: Background: Surveys from several European countries suggest a European-wide increase in the use of Complementary and Alternative Medicine (CAM). To safeguard citizens’ rights concerning their healthcare, it is critical to gain an overview of citizens’ attitudes and to understand their expectations and needs regarding CAM. Methods: A review of literature was undertaken, based on systematic searches of the following electronic databases: PubMed, Web of Science, CINHAL, AMED, PsycINFO and PsycArticles; 189 articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 133 publications
(177 reference statements)
2
53
0
5
Order By: Relevance
“…Body-based therapies thus seem to remain less accessible to low-income groups. That may be the reason why the Czech population would welcome reimbursement for manual therapies [13]. Cost as a barrier to CAM was also stated in other European studies on CAM use [14].…”
Section: Discussionmentioning
confidence: 96%
“…Body-based therapies thus seem to remain less accessible to low-income groups. That may be the reason why the Czech population would welcome reimbursement for manual therapies [13]. Cost as a barrier to CAM was also stated in other European studies on CAM use [14].…”
Section: Discussionmentioning
confidence: 96%
“…Hence, perceiving the service provider as being able, having integrity, and being benevolent might have mitigated privacy risk perception and amplified personalisation benefit perception. The preference for scientifically trained experts related to a tangible service may also be explained by the fact that when it comes to health, western consumers are accustomed to face-to-face communication [53] with qualified professionals trained in conventional medicine [54]. Often, consumers tend to choose services to which they are accustomed because such services strengthen their trust in the fact that service provision will proceed as expected [55].…”
Section: Discussionmentioning
confidence: 99%
“…(CM) is a part of the traditional medicine, commonly used and reflects the sum of knowledge, skills and practices built on experiences, beliefs and theories of different cultures. This practice is widely used worldwide; 80% in the African population and 42% among the Americans had used it at least once [2]. It was reported as well in many countries including the developing countries, Mediterranean region and Islamic societies; In Palestine, the use of at least one type of (CM) was 73%; In Lebanon, a survey documented the use of (CM) in about 30% of adults [3]; In Egypt it was found that 77.5% of adults reported the use of CM [4].…”
Section: Introductionmentioning
confidence: 99%